2007
DOI: 10.1097/01.prs.0000264402.97692.b6
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Phase I Trial of Evolence30 Collagen for Soft-Tissue Contour Correction

Abstract: Evolence30 is a new, porcine-derived collagen product based on the Glymatrix cross-linking technology that enables a safe and effective correction of the nasolabial folds. This correction lasts significantly longer than that with Zyplast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…17 The study was conducted in accordance with the International Conference on Harmonisation Guidelines for Good Clinical Practice. All patients signed the informed consent form.…”
Section: Methodsmentioning
confidence: 99%
“…17 The study was conducted in accordance with the International Conference on Harmonisation Guidelines for Good Clinical Practice. All patients signed the informed consent form.…”
Section: Methodsmentioning
confidence: 99%
“…No treatment-related adverse events were reported, although transient erythema was observed in both treated sides. 22 Lip. We identified two studies that investigated the use of collagen fillers in the lip, including one randomized controlled trial and one cohort study.…”
Section: Collagen Fillersmentioning
confidence: 97%
“…Between 2008 and 2012, some studies have been published with longer follow-up periods, that is, three to four years [32][33][34][35][36]. The need for this development is illustrated by two studies [37,38] in which it was found that semi-permanent injectable fillers remain in the skin longer than the period claimed by the manufacturer: 18 and 23 months, respectively, while the claims were 12 months. Experiences in the past with PLLA, also a biodegradable material, have already shown that late adverse effects may occur depending on the amount of material used, for example, PLLA bone plates and screws used in fixation of cheekbone fractures were found to be able to lead to swelling after about three to five years [39].…”
Section: Semi-permanent Tissue Fillersmentioning
confidence: 99%